What hampers 'political' action in environmental alternative action organizations? Exploring the scope for strategic agency under post-political conditions. (4th May 2021) - de Moor, Joost; Catney, Philip; Doherty, Brian
ABSTRACT: The proliferation of environmental alternative action organization (EAAOs) is a defining feature of present-day environmentalism. The literature on sustainable materialism has celebrated this as an appropriate, effective, and above all, political strategy. By contrast, drawing on post-political and post-ecologist critiques, some have argued that this shift signifies the de-politicisation of environmentalism because it leaves the status quo unchallenged. In this article, we argue that these opposing views can be reconciled first by considering that 'the political' has at least three different dimensions, and second by taking account of how activists reflexively navigate the different challenges posed by each of these dimensions in their strategizing. Based on an ethnographic case study of two organizations in Manchester (UK), we show that while EAAOs developing environmental alternatives may indeed be motivated by radical ideas – as suggested in literature on sustainable materialism – the contradictory demands of diffusion and agonism limit their expression through contentious action. We argue that the post-political context in which these groups operate thus has some depoliticizing impact, yet that activists consciously navigate these challenges to maximize their political impact.